Polymerization-induced phase separation as a one-step strategy to self-assemble alkanethiol-stabilized gold nanoparticles inside polystyrene domains dispersed in an epoxy matrix - Romeo, Hernan Esteban (2012)
The rational design of nanoparticle (NP)/polymer composites with advanced functional properties is based on controlling the distribution and self-assembly of NPs in the polymer matrix. In this study we report a new one-step strategy to produce the self-assembly of alkanethiol-stabilized Au NPs in one of the phases generated by polymerization-induced phase separation. The polymerization of a formulation composed of stoichiometric amounts of diglycidylether of bisphenol A (DGEBA) and m-xylylenediamine (mXDA), containing polystyrene (PS) and dodecanethiol-stabilized Au NPs as modifiers, produced the phase separation of PS and Au NPs into microdomains dispersed in the epoxy matrix. A subsequent phase separation and self-assembly of Au NPs took place inside the PS domains leading to an increase in their concentration in a region close to the interface as revealed by TEM images. SAXS spectra showed that NPs self-assembled as colloidal crystals with a body-centered cubic (bcc) structure. By an adequate selection of the amount of PS and the nature of the epoxy precursors, different morphologies of the final blend could be generated. This brings the possibility of controlling the dispersion and self-assembly of NPs in the final material.